Kinerja Penyuluhan di Nusa Tenggara Timur - Jelamu Ardu Marius; Sumardjo Sumardjo; Margono Slamet; Pang S Asngari (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2009)
The objectives of this research were to portray the influence of internal and external factors to the performance of the agricultural extension. The individual characrterization of the agricultural extension agents were the internal factors which assumed to influence toward the performance of agricultural extension and those other i.e the non formal extension education (diklat), the milieu, and the extension organization structure were the external factors. The respondents were selected by the random and purposive sampling method in the three regency as research area. Data analysis was done by using descriptive and Linear Structural Relationship (LISREL) program 8.72 by Structural Equation Modelling (SEM) models. The results of the research showed that the non formal extension education and the extension organization structure were influenced positively and significantly to the performacen of extension (external factors), but those other were not.